Associations between Mobility, Cognition, and Brain Structure in Healthy Older Adults - Demnitz, Naiara; Zsoldos, Enikő; Mahmood, Abda; Mackay, Clare E.; Kivimäki, Mika; Singh-Manoux, Archana; Dawes, Helen; Johansen-Berg, Heidi; Ebmeier, Klaus P.; Sexton, Claire E. (Frontiers in Aging Neuroscience, 2017)
Mobility limitations lead to a cascade of adverse events in old age, yet the neural and cognitive correlates of mobility performance in older adults remain poorly understood. In a sample of 387 adults (mean age 69.0±5.1 years), we tested the relationship between mobility measures, cognitive assessments and MRI markers of brain structure. Mobility was assessed in 2007-2009, using gait, balance and chair-stands tests. In 2012-2015, cognitive testing assessed executive function, memory and processing-speed; gray matter volumes (GMV) were examined using voxel-based morphometry, and white matter microstructure was assessed using tract-based spatial statistics of fractional anisotropy (FA), axial diffusivity (AD) and radial diffusivity (RD). All mobility measures were positively associated with processing-speed. Faster walking speed was also correlated with higher executive function, while memory was not associated with any mobility measure. Increased GMV within the cerebellum, basal ganglia, post-central gyrus and superior parietal lobe was associated with better mobility. In addition, better performance on the chair-stands test was correlated with decreased RD and AD. Overall, our results indicate that, even in non-clinical populations, mobility measures can be sensitive to sub-clinical variance in cognition and brain structures.